PENGARUH PUPUK KOTORAN JANGKRIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN EDAMAME (Glycine max (L.) Merill) - Irvansyah Rizki Pratama; Jumar Jumar; Rabiatul Wahdah (Universitas Lambung Mangkurat, 2019)
Edamame is included category vegetable plants (green soybean vegetable) with high economic value and has a fairly good nutrient content for body health. However, soybean production, especially edamame plants in the Banjarbaru area is still minimal so the potential for the development of edamame plants is very large in the South Kalimantan region, especially the Banjarbaru area. As for one way to increase the production of edamame plants by fertilizing. The use of fertilizers is divided into 2 types, namely inorganic and organic fertilizers. The provision of inorganic fertilizers is easy to do with the right amount, but the price of inorganic fertilizers is currently still relatively expensive, so it will increase production costs. Based on the above, the use of organic fertilizers can be a solution to increase the production of cheap and environmentally friendly edamame plants by utilizing cricket manure waste. During this time cricket droppings have not been fully utilized by cricket farmers. Taking into account the factor of fertilizer prices and waste from cricket manure, fertilizer from cricket droppings is raised which is expected to be an alternative to organic fertilizer. This study aims to determine the effect of cricket manure and the effect of multiple doses on the growth and yield of edamame plants. This research was conducted in March to June 2019 in the Kebonan Mas Untung Field, Gunung Kupang Cempaka, Banjarbaru South Kalimantan. The design used is a completely randomized design (RBD) of one factor, namely the dose of fertilizer. The results showed that the application of cricket manure had a significant effect on pod wet weight, plant height and number of leaves. The best dose in increasing plant height, number of leaves and wet weight of pods was K2 treatment 5 tons / ha.